Low plastic ingestion rate in Atlantic cod (Gadus morhua) from Newfoundland destined for human consumption collected through citizen science methods. Issue 1 (15th December 2016) - Liboiron, Max; Liboiron, France; Wells, Emily; Richárd, Natalie; Zahara, Alexander; Mather, Charles; Bradshaw, Hillary; Murichi, Judyannet
Abstract: Marine microplastics are a contaminant of concern because their small size allows ingestion by a wide range of marine life. Using citizen science during the Newfoundland recreational cod fishery, we sampled 205 Atlantic cod ( Gadus morhua ) destined for human consumption and found that 5 had eaten plastic, an ingestion prevalence rate of 2.4%. This ingestion rate for Atlantic cod is the second lowest recorded rate in the reviewed published literature (the lowest is 1.4%), and the lowest for any fish in the North Atlantic. This is the first report for plastic ingestion in fish in Newfoundland, Canada, a province dependent on fish for sustenance and livelihoods. Highlights: Plastic ingestion rate of 2.4% for Atlantic cod (n = 205) First recorded baseline for fish in Newfoundland, Canada This plastic ingestion prevalence rate is among the lowest recorded to date. Used citizen science to collect GI tracts from fish destined for human consumption